VARIABILITY FEATURES OF THE RADIO SOURCE OT 081 IN CENTIMETER WAVELENGTH RANGE - Sukharev, A. L.; Aller, Margo F. (Одеські астрономічні публікації, 2014)
OT 081 – BL Lac object, intensively studied for many years in a wide range of the electromagnetic spectrum. We used observational data for 1999-2011 years, obtained on radio telescope at Michigan State University (UMRAO) at frequencies 14.5, 8, 4.8 GHz.For the study variability of the radio source used wavelet method of time series analysis. The values of main periods at three frequencies are ~2.6 and 1.2 years. The shortest periods with values ~0.9, 0.6, 0.4 years were shown in small time intervals (1.5 years). For harmonic components isolated by filtration, determined delay between radio frequencies. Obtained comparison of change between periods fluctuations of radio fluxes and dynamics in the radio jet (image VLBI Mojave, 15.4 GHz).